Sámi and Norwegian nurses’ perspectives on nursing care of Sámi patients: a focus group study on culturally safe nursing - Sivertsen, Nina; Bongo, Berit Andersdatter; Mehus, Grete (International Journal of Circumpolar Health, 2021)
Sámi people report less satisfaction with healthcare services than the majority population in Norway, and report that they seldom encounter culturally adapted health services. This study investigates Sámi and Norwegian nurses’ perspectives on culturally respectful and appropriate caring for Sámi patients in northern Norway. Six focus groups were conducted: three with Sámi-speaking nurses (n = 13) and three with Norwegian-speaking nurses (n = 10). Data were collected and analysed in line with Thorne’s interpretive descriptive methodology. Three overarching themes emerged from the interviews: (i) the importance nurses gave to establishing a connection and building trust with Sámi patients; (ii) nurses’ perceptions that in comparison to Norwegian patients Sámi patients could be less confrontational and direct, but that differences weren’t always apparent and (iii) the importance nurses described to understanding the cultural context of their Sámi patients. This study showed that Sámi and Norwegian nurses working in northern Norway were largely perceptive about and respectful of cultural differences between Sámi and Norwegian patients. Some emphasised, though, that Sámi patients were diverse and that interpersonal differences were as or more important than cultural differences. Some also felt that more understanding of Sámi culture would be helpful for enabling culturally respectful nursing care.